2015
DOI: 10.22216/jit.2015.v9i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengobatan Stroke dengan Jenis Stroke dan Jumlah Jenis Obat

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Another significant factor in hospital medicines cost is the length of stay, as also stated by other previous research [9,13,14]. Patients receiving more medicines (>10) were hospitalized longer than those receiving less than five medicines [20].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Another significant factor in hospital medicines cost is the length of stay, as also stated by other previous research [9,13,14]. Patients receiving more medicines (>10) were hospitalized longer than those receiving less than five medicines [20].…”
Section: Discussionmentioning
confidence: 70%
“…The average number of medicines item is 10.52 items. Similar research showed the number of medicines items for stroke patients as more than 10, which is considered as high [20]. High use of medicines is vulnerable to medicines interaction risk considering the age of patients that are mainly geriatric patients having a low function of kidney and liver which influence the pharmacodynamics and pharmacokinetics of medicines consumed.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Stroke bisa menyerang semua kelompok umur tetapi mayoritas stroke menyerang pada lelompok usia lanjut. Perawatan jangka panjang dibutuhkan dalam pengobatan stroke, perlu adanya kerjasama antara dokter, perawat, apoteker, pasien dan keluarga pasien sehingga untuk bisa mencapai hasil yang baik [11]. Rehabilitasi pada pasien stroke dilakukan setelah pasien tersebut sudah dinyatakan sembuh secara medis dengan indikator kondisi klinis neurologis dan hemodinamik dalam keadaan stabil [12].…”
Section: Pendahuluanunclassified